Técnicas básicas con el balón y su incidencia en el aprendizaje del baloncesto para los estudiantes de básico superior de la Unidad Educativa Quevedo - Fernandes Morales, Kleber Omar (2016)
This thesis project is structured in several chapters, which understands definition of the basketball, History, generalities, methodology, and technical of the domain of the ball, etc. Mainly the project is based in the basic techniques with the ball and its incidence in the learning of the basketball for the students of Basic Superior of the Educational Unit Queued, located in The Ríos' county, related with the practice of this sport in the aforementioned context. In the suitable investigation project one worked mainly in the development of the basic techniques and the learning of the basketball, after this we demonstrate with comparative squares the progress of the children improving their physical capacities and helping to the development and corporal growth, and also to manifest that in this Canton good human element exists to foment the sport activity and especially the basketball. Therefore, this graduation work implies the validation of each one of the processes scored in the basic techniques and learning of the basketball through the application of the proposal and obtained results